2016
DOI: 10.1111/epi.13418
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for subsequent febrile seizures in the FEBSTAT study

Abstract: Objectives To identify risk and risk factors for developing a subsequent febrile seizure (FS) in children with a first febrile status epilepticus (FSE) compared to a first simple febrile seizure (SFS). To identify home use of rescue medications for subsequent FS. Methods Cases included a first FS that was FSE drawn from FEBSTAT and Columbia cohorts. Controls were a first SFS. Cases and controls were classified according to established FEBSTAT protocols. Cumulative risk for subsequent FS over a five year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
21
2
4
Order By: Relevance
“…Many studies have now demonstrated that early exposure of the brain to immune responses can have varied and persistent consequences on adult physiology [99102]. Febrile seizures (FS) and febrile status epilepticus in children is a risk factor for developing epilepsy later in life [103], which may be induced by fever often associated with inflammation and infection [47]. Although the mechanisms underlying FS remains unclear, it is thought that cytokines play a key role in its development [104].…”
Section: Inflammation In Epileptogenesismentioning
confidence: 99%
“…Many studies have now demonstrated that early exposure of the brain to immune responses can have varied and persistent consequences on adult physiology [99102]. Febrile seizures (FS) and febrile status epilepticus in children is a risk factor for developing epilepsy later in life [103], which may be induced by fever often associated with inflammation and infection [47]. Although the mechanisms underlying FS remains unclear, it is thought that cytokines play a key role in its development [104].…”
Section: Inflammation In Epileptogenesismentioning
confidence: 99%
“…However, the FEBSTAT study revealed that some virus may be associated with the occurrence of febrile status epilepticus. 6 Specifically, the authors identified an association between the presence of human herpes virus type 6B (HHV-6B) DNA and RNA in serum of children with febrile status epilepticus. 7 Routine viral studies are still not recommended in the evaluation of SFS as the results do not modify the clinical impression and do not change the treatment or prognosis.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…They are classified as complex if they are prolonged (>10 minutes), focal, or multiple. 8,9 FSE (30 minutes) is considered the extreme end of the complex febrile seizure spectrum.…”
Section: Definitionmentioning
confidence: 99%
“…As mentioned before, having FSE is a risk factor for having subsequent FSE and febrile seizures in general. 9 It has also been associated with the development of epilepsy, specifically TLE. The time between FSE and the development of MTLE can be greater than 10 years and therefore this is hard to prove in prospective studies.…”
Section: Prognosismentioning
confidence: 99%